Space Demonstration of All-Solid-State Lithium-Ion Batteries Aboard the International Space Station - Yu Miyazawa; Takanobu Shimada; Tetsuhito Fuse; Shuhei Shimada; Sousuke Nishiura; Hidetake Okamoto; Tetsuya Okawa; Takeshi Hoshino; Osamu Kawasaki; Hitoshi Naito (Aerospace, 2025)
All-solid-state lithium-ion batteries (ASSBs) have a wide operating temperature range (−40 °C to +120 °C) and are expected to be applied to lunar exploration, which has become increasingly active in recent years. Since a ground development test confirmed that ASSBs are tolerant of the space environment, in this study, a space demonstration test is conducted on the International Space Station (ISS). The battery was exposed in the ISS Exposed Section for 434 days. A total of 562 charge–discharge cycle tests were conducted, in addition to basic charge–discharge characterization, with no significant degradation observed in the charge–discharge characteristics or battery appearance. These results confirm that the battery operates reliably even in a complex space environment. This test confirmed that the lifetime characteristics of ASSBs can be estimated via ground-based charge–discharge characteristics, encouraging their potential application in space exploration.